GHIBAH DALAM ENTERTAINMENT PERSPEKTIF HADIS (APLIKASI TEORI DOUBLE MOVEMENT FAZLUR RAHMAN) - Layyinatus Sifa (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Citizen life in modern society wich have many activities makes them need some entertainment. Either from social media, recreation or televison show. Every show arranged as creative as can for interest the audience and get the high rate. One of them is rality show wich give any informations about entertainment called infotainment. In this show, there are many information about many things, such as the life of entertainer, privacy live and disgrace of household. And there are many information that contain of bringing into conflict one to another. And in along time this show containing of “ghibah”in a modern version without releazied from the audience. How is the rules of “ghibah” in this modern context and how we will apply the Sunnah of Muhammad about avoiding ghibah in millenial era using the teory of double movement from Fazlur Rahman. Keyword: ghibah, Infotainment, Hadis, Fazlur Rahman Kehidupan masyarakat modern yang disibukkan dengan bermacam aktifitas membuat masyarakat haus akan berbagai jenis hiburan. Mulai dari media sosial, tempat rekreasi sampai acara televisi. Berbagai acara disusun sekreatif mungkin untuk menarik penonton dan mendapatkan rating yang tinggi. Termasuk salah satunya acara inforamsi tentang dunia entertainment atau yang dikenal dengan istilah infotainment. Dalam acara tersebut sering diberitakan kehidupan tentang pemain dunia entertainment, mulai kehidupan pribadi, keluarga sampai aib rumah tangga. Tak sedikit juga berita yang terkesan mengadu domba antar tokoh publik tersebut. Semakin lama acara ini terkesan seperti “ghibah” dalam versi modern tanpa disadari oleh masyarakat yang menikmatinya. Bagaimana sebenarnya hukum “ghibah” dalam acara tersebut, dan bagaimana kita mengaplikasikan hadis nabi tentang larangan ghibah dalam era millenial sekarang dengan teori doble movemnet Fazlur Rahman. Kata kunci: Ghibah, Infotainment, Hadis, Fazlur Rahman